Suppressive effect of arginine and sodium fluoride on enamel calcium loss and antibiofilm activity on mature oral microcosm biofilms - Méndez, Daniela Alejandra Cusicanqui; Cuellar, Maricel Rosário Cardenas; de Andrade, Flaviana Bombarda; Wang, Linda; Buzalaf, Marília Afonso Rabelo; Pessan, Juliano Pelim [UNESP]; Cruvinel, Thiago; Sampaio, Caio [UNESP] (Taylor & Francis, 2025)
This study investigated the effects of arginine, with/without sodium fluoride (NaF), on mature oral microcosm biofilms and enamel calcium loss (ECL). Saliva-derived biofilms grown on bovine enamel for three days were subsequently assigned to their respective test groups and cultured until day seven (n = 9/group). Biofilm parameters and ECL were assessed. Reductions in the number of lactobacilli were observed with arginine at 2.5%/8% concentrations, with/without NaF, while 8% arginine, with/without NaF, reduced the number of all microorganism groups. The addition of 8% arginine and combinations of arginine with NaF reduced biofilm vitality. While all treatments resulted in a reduction of α-EPS, 8% arginine showed the most pronounced effect, being the only treatment to decrease β-EPS compared to the control. Reductions in ECL were achieved by 8% arginine, with/without NaF, 2.5% with NaF, and NaF, compared with the negative control (untreated biofilms). These findings demonstrated that arginine and NaF increased antibiofilm activity against mature biofilms, reducing ECL.